Knowledge, attitudes, and practices regarding COVID-19 and mental health status among college students in China: a cross-sectional study - Li, Yi-Hua; Wen, Tao; Cui, Yin-Shi; Huang, Zhe-Hu; Liu, Yan-Qun (Frontiers in Public Health, 2023)
Background: During the prevalence of coronavirus disease 2019 (COVID-19), little was known about the knowledge, attitude, practice(KAP) about COVID-19 and psychological status of college students in minority areas. This study aimed to evaluate the knowledge, attitudes, and practices (KAP) of college students in minority areas of China toward COVID-19 and to provide a scientific basis for health education and policy formulation. Methods: From October 28th to November 6th, 2021, a cross-sectional study was conducted with 5272 college students to examine KAP and its effects on mental health. Results: Regarding COVID-19 knowledge, the overall awareness rate was 24.11% (1,271). Regarding health attitudes, most students had positive attitudes about COVID-19 prevention and control (94.95%), and females had higher positive attitudes than males (OR: 1.920; CI: 1.494 2.469). Regarding preventive behaviors, more than half of the students took preventive measures (53.48%), and freshmen had the highest health behavior scores. In terms of psychological status, there were fewer females with depression and stress than males. Conclusion: College students in minority areas have positive health attitudes; however, their knowledge of COVID-19 prevention and control is low. Moreover, their precautionary behaviors are insufficient, and they have many negative emotions.